Artificial Intelligence and Nuclear Command and Control. Issue 3 (4th May 2019) - Fitzpatrick, Mark
Abstract : An IISS tabletop exercise showed how an AI arms race could reduce strategic stability as nuclear-weapons states become more reliant on artificial intelligence.